Development of Formative Assessment by Utilizing Quizizz in Increasing Student Learning Interest - Willyan Iswandi; Henny Indrawati; Gimin Gimin (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2026)
This study aims to develop a Quizizz-based formative assessment in Integrated Social Studies class IX as an effort to improve the effectiveness of learning evaluation. The background of this research is based on the limited use of technology in assessment activities in schools and the need for evaluation media that are interesting, interactive, and in accordance with the characteristics of today's students. This research uses the ADDIE development model which includes five stages: analysis, design, development, implementation and evaluation. In the analysis stage, researchers identified needs through interviews with teachers and analysis of lesson plan documents. The design stage included designing the question format, quiz display, and prototyping. At the development stage, the assessment was validated by three experts, namely assessment, media, and language experts. The validation results showed that the developed assessment was in the very valid category and very feasible to use. The implementation stage showed an increase in implementation from the first meeting to the second meeting. Evaluation was conducted formatively and summatively to review the entire development process. The results showed that Quizizz-based formative assessment is effective in social studies learning because it is able to increase student participation, provide immediate feedback, and make the evaluation process more interesting. This finding shows the importance of integrating digital technology in learning assessment as part of educational innovation that is adaptive to the times